THE WAYS FOR ACTIVATING PUPILS' COGNITIVE ACTIVITY AND MENTAL CAPACITY - D. V. Sukhorukov; L. A. Sorokina (Russian State Vocational Pedagogical University, 2015)
The paper discusses various methods promoting the cognitive activity of secondary school pupils, whose psycho-physical conditions are adversely affected by the changing realities of educational process: its acceleration, growing amount of the required information, increasing number of disciplines, declining moral of the educational environment, etc. The authors emphasize the need for the urgent systematic and complex measures for pupils' health promotion and working capability restoration with the reference to the age profile and specificity of the particular educational environment. The definitions of the main categories and ways, activating the knowledge acquisition, are given along with the basic groups of methods facilitating the mental activity. They include traditional didactic methods; psycho-emotional methods, used for emotional adjustment and optimization of pupils' perception; and pharmacological methods for increasing the mental work capacity by means of various medications. In conclusion, the authors demonstrate a project model of the complex method for activating the cognitive abilities of secondary school pupils.